Edukasi Masyarakat Desa Hajimena dalam Pembuatan Biopori dan Pengelolaan Corn Ribs Sebagai Makanan - Ramdani, Andika Hamdiyana; Maharani, Dian Magista; Mumtaz, Salman; Alfiyani, Ririn; Sihombing, Joy Nathanael (Fakultas Ilmu Sosial dan ilmu Politik, 2024)
Climate change has become a global problem affecting many sectors, including household sanitation. Poor sanitation, especially inadequate management of organic waste, contributes to greenhouse gas emissions that exacerbate climate change. This community service is carried out with the aim of providing solutions through organic waste management and climate-friendly food processing. This activity focuses on socialization to the community in one of the villages in Lampung province, namely Hajimena Village, Natar District, South Lampung Regency regarding the importance of implementing simple but effective technologies, such as biopori absorption holes, It serves to treat organic waste into compost that is useful for improving groundwater absorption. In addition, this service also introduces processed corn as a product of climate-friendly foods. The processed food is Corn Ribs, which is easy to make and can be a microbusiness opportunity. With the implementation of biopore technology and climate-friendly food innovation, it is hoped that people can contribute to reducing the negative effects of climate change, increasing food security, and reducing organic waste.